Marketing Strategy Analysis Based on the 4P Theory: A Case Study of Sephora - Zhou, Yingran (Transactions on Economics, Business and Management Research, 2024)
Sephora is an old brand, it has been known to the public since its opening, its products sell well, and decades later it is still popular around the world, and its sales have been rising, thanks to its unique 4P marketing strategy. Sephora's marketing strategy has achieved great success, and this paper will analyze their strategy by the way of literature analysis. Sephora, as a giant in the beauty industry, owns many brands and has many customers, which can be attributed to their marketing strategy. Sephora's marketing strategy mainly focuses on a wide audience, high tolerance, both online and offline stores, product diversification, self-service shopping to provide customers with a comfortable shopping environment, cultivate customer loyalty, and a wide price range. Sephora has a clear positioning and operates numerous chain stores globally. It also provides customers with specialized services to make customers clearer about their needs and strengthen customer loyalty with unique services. Sephora has gained a large number of followers with its wide range of prices, product diversification, geographical location and proper promotion.